Analisis Peranan Budaya Organisasi dan Disiplin Kerja Terhadap Upaya Peningkatan Kinerja Karyawan - Syahyuni, Dedy (JURNAL ADMINISTRASI KANTOR, 2022)
In every company or organization there must be a color or differentiator that makes the organization or company look unique when viewed and compared to other organizations or companies. This is formed from how the top leaders and founders of the organization make decisions from the beginning of the organization or company being founded, this is called organizational culture. Organizational culture shapes the character and mindset of the employees in the organization or company. A good culture will form good employee performance and synergies in e very job and good relations between one employee and another and vice versa. Therefore, organizational culture is something that should be considered by human resource management in an effort to improve performance. Apart from that, organizational culture also affects the improvement of employee work discipline, and directly or indirectly work discipline also affects employee performance. So it can be seen that organizational culture and work discipline are two things that affect the effort to improve performance. This paper tries to explain how the relationship between the three variabels in a company where the respondents are 40 people and the method used is a quantitative method and in calculations using the SPSS application with an error rate of 5%.     Keywords : Culture, Discipline, Performance.